The role of digital media in the popularization of scientific knowledge: realities and challenges (Herald of Journalism, 2022)
The article deals with the problems of modern interaction between science and innovative technologies of mass media. Аn important role in the popularization of promoting scientific research is played by the media, which broadcast scientific knowledge to society. However, to date, scientific research is of little interest to journalists. The author describes the possibilities of digital journalism in the promotion of scientific knowledge and the involvement of governmental agencies in the activities of Kazakhstani scientists. The purpose of the article is to consider the possibilities of the multimedia environment in creating a high-quality information base on scientific developments and their introduction into the modern economy and society. Digital media of Kazakhstan should actively participate in the promotion of current knowledge, offering various forms of presentation of scientific and popular-science information.The scientific significance of the article consists in an attempt to take a new look at the popularization of scientific knowledge; new functions of the media in the context of promoting a civilized worldview. The research methodology provides a systematic approach, a method of comparative analysis, classification. The aim of the research is to identify new challenges facing the media in the modern period within the framework of scientific and popular-science discourse. Mass media contribute to the popularity of scientific knowledge and form a special attitude to science as a phenomenon on which the existence of modern civilization depends, which determines the scientific value of this article. The practical significance lies in the possibility of introducing the results of the research into teaching at journalism faculties in specialized and elective disciplines, as well as in advanced training courses for journalists specializing in the topic of science.Keywords: journalism, science, digital journalism, digital media, scientific journalism, popular- science journalism.